Ablation of Cyclooxygenase-2 in Forebrain Neurons is Neuroprotective and Dampens Brain Inflammation after Status Epilepticus - Serrano, G. E.; Lelutiu, N.; Rojas, A.; Cochi, S.; Shaw, R.; Makinson, C. D.; Wang, D.; FitzGerald, G. A.; Dingledine, R. (The Journal of neuroscience, 2011)
Cyclooxygenase-2 (COX-2), a source of inflammatory mediators and a multifunctional neuronal modulator, is rapidly induced in select populations of cortical neurons after status epilepticus. The consequences of rapid activity-triggered induction of COX-2 in neurons have been the subject of much study and speculation. To address this issue directly, we created a mouse in which COX-2 is conditionally ablated in selected forebrain neurons. Results following pilocarpine-induced status epilepticus indicate that neuronal COX-2 promotes early neuroprotection and then delayed neurodegeneration of CA1 pyramidal neurons, promotes neurodegeneration of nearby somatostatin interneurons in the CA1 stratum oriens and dentate hilus (which themselves do not express COX-2), intensifies a broad inflammatory reaction involving numerous cytokines and other inflammatory mediators in the hippocampus, and is essential for development of a leaky blood–brain barrier after seizures. These findings point to a profound role of seizure-induced neuronal COX-2 expression in neuropathologies that accompany epileptogenesis.